Olivetol’s Effects on Metabolic State and Gut Microbiota Functionality in Mouse Models of Alimentary Obesity, Diabetes Mellitus Type 1 and 2, and Hypercholesterolemia - Anastasia A. Zabolotneva; Katerina E. Popruga; Valentin V. Makarov; Sergei M. Yudin; Andrei M. Gaponov; Sergei A. Roumiantsev; Aleksandr V. Shestopalov (Biomedicines)
Background: Disorders of glucose and lipid metabolism, such as obesity, diabetes mellitus, or hypercholesterolemia, can cause serious complications, reduce quality of life, and lead to increased premature mortality. Olivetol, a natural compound, could be proposed as a promising therapeutic agent for preventing, treating, or alleviating metabolic complications of such pathological conditions. Methods: In this study, the researchers conducted a broad parallel investigation of olivetol’s effects on metabolic state and gut microbiota functionality in mouse models of alimentary obesity, diabetes mellitus type 1 and 2, and hypercholesterolemia. Results: According to the results of the study, olivetol caused a lowering of body weight in C57Bl6 mice fed a high-fat diet and in ldlr(−/−) mice, decreased serum glucose levels in db/db mice, improved lipid metabolism in ldlr(−/−) mice, and prevented inflammatory infiltration of the pancreas and loss of insulin secretion in NOD mice. In addition, olivetol affected the composition and functional activity of gut microbiota communities, inducing an expansion of probiotic species such as Akkermansia muciniphila and Bacteroides acidifaciens and depleting the representation of pathobionts such as Prevotella, although olivetol supplementation did not influence the diversity or richness of the communities. Conclusions: These results suggest that olivetol is a promising therapeutic agent for preventing, treating, or alleviating the metabolic complications of obesity, diabetes mellitus type 1 and 2, and hypercholesterolemia; however, more investigations are required in order to attain a full understanding of its physiological effects.